Prosecution among Friends : Presidents, Attorneys General, and Executive Branch Wrongdoing. - Yalof, David Alistair (Joseph V. Hughes, Jr. and Holly O. Hughes series on the presidency and leadership., 2012)
Can Justice Department officials effectively investigate wrongdoing within their own administration without relying on an independent counsel? In Prosecution among Friends political scientist David Alistair Yalof explores the operation of due process as it is navigated within the office of the attorney general and its various subdivisions. The attorney general holds a politically appointed position within the administration and yet, as the nation's highest ranking law enforcement officer, is still charged with holding colleagues and superiors legally accountable. That duty.